2001
DOI: 10.1186/1471-2105-2-7
|View full text |Cite
|
Sign up to set email alerts
|

The Distributed Annotation System

Abstract: Background: Currently, most genome annotation is curated by centralized groups with limited resources. Efforts to share annotations transparently among multiple groups have not yet been satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(127 citation statements)
references
References 11 publications
0
127
0
Order By: Relevance
“…Using the Perl-based Proserver (Finn et al 2007), a Distributed Annotation System (Dowell et al 2001) (DAS) feature server was implemented that allows the identified peptides stored in the GenoMS-DB database (Fig. 1) to be visualized as tracks in various genome browsers and curation tools.…”
Section: Distributed Annotation Systemmentioning
confidence: 99%
“…Using the Perl-based Proserver (Finn et al 2007), a Distributed Annotation System (Dowell et al 2001) (DAS) feature server was implemented that allows the identified peptides stored in the GenoMS-DB database (Fig. 1) to be visualized as tracks in various genome browsers and curation tools.…”
Section: Distributed Annotation Systemmentioning
confidence: 99%
“…Several web interface improvements and a distributed annotation system [25] server are in progress. Protein family classification is being investigated using machine learning and the diverse predictions that are available in Unison.…”
Section: Discussionmentioning
confidence: 99%
“…This service can be used for exploration of ligandbinding sites and small three-dimensional structural motifs across the entire PDB archive. PDBeMotif also integrates sequence-based annotation information using DAS technology (Dowell et al, 2001) and allows users to compare this information with annotations based on the three-dimensional structure. It is possible to examine the ligand-binding characteristics of a single protein or of groups of proteins based on classifications such as EC (Fleischmann et al, 2004), Pfam (Finn et al, 2010), CATH (Greene et al, 2007) and SCOP.…”
Section: Advanced Servicesmentioning
confidence: 99%